Identifying the exercise-based support needs and exercise programme preferences among men with prostate cancer during active surveillance: A qualitative study. (August 2019) - McIntosh, Megan; Opozda, Melissa; Galvão, Daniel A.; Chambers, Suzanne K.; Short, Camille E.
Abstract: Purpose: This study aims to investigate the attitudes and preferences men on active surveillance for prostate cancer have regarding exercise and exercise-based support. Exercise outcomes align with traditionally masculine values, can improve mental and physical health, and may even slow early stage prostate cancer progression. However, attitudes and preferences towards exercise and exercise support are unexplored in men on active surveillance. Methods: Semi-structured qualitative interviews were conducted with participants (13 males with a history of active surveillance for prostate cancer; 5 female partners). Interviews were conducted either by telephone or in person and audiotaped, transcribed verbatim, and thematically analysed. Results: Several key themes were identified relating to the two research aims: 'Attitudes and Preferences towards Exercise, and 'Attitudes and Preferences towards Exercise Support'. Despite all men engaging in exercise, the majority did not meet the recommended guidelines for cancer survivors. The majority of men either were interested in receiving exercise support or had previously received it, often recommending this for all men on active surveillance. There were varied preferences regarding delivery modality (i.e., online or face to face), the inclusion of partners, and group versus individual formats. Conclusions: This study provides a novel insight into the attitudes and preferences of men on active surveillance regarding exercise and support. This research will help the development of acceptable and accessible person-centred support for men on active surveillance. However, further research is needed to evaluate the efficacy of different delivery modalities in this population. Highlights: Exercise during active surveillance may improve physical and mental health. Men on active surveillance are interested in exercise and receiving exercise-based support. Exercise support programs must emphasise the exercise oncology guidelines. Internet may be an acceptable modality for delivering exercise-based support.